A semi‐quantitative approach for the rapid screening and mass profiling of naphthenic acids directly in contaminated aqueous samples. (1st December 2015) - Duncan, Kyle D.; Letourneau, Dane R.; Vandergrift, Gregory W.; Jobst, Karl; Reiner, Eric; Gill, Chris G.; Krogh, Erik T.
Abstract : We report the use of a direct sampling, online analytical approach for the determination of acid extractable naphthenic acids in complex aqueous samples, known as condensed phase membrane introduction mass spectrometry (CP‐MIMS). The technique employs a capillary hollow fibre semi‐permeable membrane probe configured for immersion into a pH adjusted sample. A continuously flowing methanol acceptor phase transfers naphthenic acids to an electrospray ionization source, operated in negative ion mode, whereupon they are analysed by mass spectrometry as [M–H] − ions. High‐resolution mass spectrometry is used to characterize the influence of sample pH on membrane transport of multiple components of complex naphthenic acid mixtures. We demonstrate the use of CP‐MIMS for semi‐quantitative analysis of real‐world samples using selected ion monitoring and full scan mass spectra at unit mass resolution. The technique has also been employed to continuously monitor the temporal evolution in the mass profile and concentrations of individual naphthenic acid isomer classes in heterogeneous solutions during adsorption processes. Copyright © 2015 John Wiley & Sons, Ltd.